Holocene Key-Marker Tephra Layers in Kamchatka, Russia - Braitseva Olga A.; Ponomareva Vera V.; Sulerzhitsky Leopold D.; Melekestsev Ivan V.; Bailey John (Quaternary Research, 1997)
Detailed tephrochronological studies in Kamchatka Peninsula, Russia, permitted documentation of 24 Holocene key-marker tephra layers related to the largest explosive eruptions from 11 volcanic centers. Each layer was traced for tens to hundreds of kilometers away from the source volcano; its stratigraphic position, area of dispersal, age, characteristic features of grain-size distribution, and chemical and mineral composition confirmed its identification. The most important marker tephra horizons covering a large part of the peninsula are (from north to south; ages given in 14C yr B.P.) SH2(≈1000 yr B.P.) and SH3(≈1400 yr B.P.) from Shiveluch volcano; KZ (≈7500 yr B.P.) from Kizimen volcano; KRM (≈7900 yr B.P.) from Karymsky caldera; KHG (≈7000 yr B.P.) from Khangar volcano; AV1(≈3500 yr B.P.), AV2(≈4000 yr B.P.), AV4(≈5500 yr B.P.), and AV5(≈5600 yr B.P.) from Avachinsky volcano; OP (≈1500 yr B.P.) from the Baraniy Amfiteatr crater at Opala volcano; KHD (≈2800 yr B.P.) from the “maar” at Khodutka volcano; KS1(≈1800 yr B.P.) and KS2(≈6000 yr B.P.) from the Ksudach calderas; KSht3(A.D. 1907) from Shtyubel cone in Ksudach volcanic massif; and KO (≈7700 yr B.P.) from the Kuril Lake-Iliinsky caldera. Tephra layers SH5(≈2600 yr B.P.) from Shiveluch volcano, AV3(≈4500 yr B.P.) from Avachinsky volcano, OPtr(≈4600 yr B.P.) from Opala volcano, KS3(≈6100 yr B.P.) and KS4(≈8800 yr B.P.) from Ksudach calderas, KSht1(≈1100 yr B.P.) from Shtyubel cone, and ZLT (≈4600 yr B.P.) from Iliinsky volcano cover smaller areas and have local stratigraphic value, as do the ash layers from the historically recorded eruptions of Shiveluch (SH1964) and Bezymianny (B1956) volcanoes. The dated tephra layers provide a record of the most voluminous explosive events in Kamchatka during the Holocene and form a tephrochronological timescale for dating and correlating various deposits.